Extension of oil biosynthesis during the mid‐phase of seed development enhances oil content in Arabidopsis seeds. Issue 5 (26th October 2015) - Kanai, Masatake; Mano, Shoji; Kondo, Maki; Hayashi, Makoto; Nishimura, Mikio
Summary: Regulation of oil biosynthesis in plant seeds has been extensively studied, and biotechnological approaches have been designed to increase seed oil content. Oil and protein synthesis is negatively correlated in seeds, but the mechanisms controlling interactions between these two pathways are unknown. Here, we identify the molecular mechanism controlling oil and protein content in seeds. We utilized transgenic Arabidopsis thaliana plants overexpressing WRINKLED1 ( WRI1 ), a master transcription factor regulating seed oil biosynthesis, and knockout mutants of major seed storage proteins. Oil and protein biosynthesis in wild‐type plants was sequentially activated during early and late seed development, respectively. The negative correlation between oil and protein contents in seeds arises from competition between the pathways. Extension of WRI1 expression during mid‐phase of seed development significantly enhanced seed oil content. This study demonstrates that temporal activation of genes involved in oil or storage protein biosynthesis determines the oil/protein ratio in Arabidopsis seeds. These results provide novel insights into potential breeding strategies to generate crops with high oil contents in seeds.